Strain-induced spatially indirect exciton recombination in zinc-blende/wurtzite CdS heterostructures - Li, Dehui (2020)
Strain engineering provides an effective mean of tuning the fundamental properties of semiconductors for electric and optoelectronic applications. Here we report on how the applied strain changes the emission properties of hetero-structures consisting of different crystalline phases in the same CdS nanobelts. The strained portion was found to produce an additional emission peak on the low-energy side that was blueshifted with increasing strain. Furthermore, the additional emission peak obeyed the Varshni equation with temperature and exhibited the band-filling effect at high excitation power. This new emission peak may be attributed to spatially indirect exciton recombination between different crystalline phases of CdS. First-principles calculations were performed based on the spatially indirect exciton recombination, and the calculated and experimental results agreed with one another. Strain proved to be capable of enhancing the anti-Stokes emission, suggesting that the efficiency of laser cooling may be improved by strain engineering.